PENGARUH PEMBERIAN AIR REBUSAN DAUN KELOR (MORINGAOLEIFERA) TERHADAP PENURUNAN KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 PADA MASYARAKAT DI DESA HUTARAJA KECAMATAN DOLOK SANGGUL - Ruth Olyvia Pakpahan; Rostime Hermayerni Simanullang (Universitas Murni Teguh, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disease with an increasing prevalence. In addition to pharmacological therapy, nonpharmacological approaches such as the use of moringa leaves (Moringa oleifera) have the potential to reduce blood glucose levels. The objective This study is To determine the effect of moringa leaf boiled water on blood glucose levels in patients with Type Diabetes Mellitus in Hutaraja Village Dolok Sanggul Distrct. The methodes This study preexperimental study employed a one-group pre-test and post-test design involving. The population 28 respondents selected through purposive sampling. The intervention consisted of administering moringa leaf boiled water once daily for 7 days. Data analysis was conducted using the Shapiro–Wilk test and paired sample t-test. The results of the mean blood glucose levels after the intervention were lower than before the intervention, with a p-value <0.05. the conculsion is Moringa leaf boiled water has a significant effect on reducing blood glucose levels in patients with Type 2 Diabetes Mellitus and can be used as a complementary non-pharmacological therapy.